2013
DOI: 10.1093/infdis/jit424
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Impairs Control of Mycobacterium tuberculosis Coinfection Through a Type I Interferon Receptor–Dependent Pathway

Abstract: Influenza followed by severe acute bacterial pneumonia is a major cause of mortality worldwide. Several mechanisms account for this enhanced susceptibility, including increased production of type I interferon (IFN). In individuals infected with Mycobacterium tuberculosis, the influence of acute viral infections on tuberculosis progression is unclear. We show that prior exposure of mice to influenza A virus, followed by M. tuberculosis infection, leads to enhanced mycobacterial growth and decreased survival. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 14 publications
5
118
5
1
Order By: Relevance
“…This leads to excessive type I IFN expression that in turn causes increased bacterial replication and pathology, thus modelling the type I IFN-associated uncontrolled active disease that occurs in a subset of TB patients 2022 . c , Likewise, experimental induction of type I IFNs by pICLC or viral co-infections 33 creates a detrimental environment with uncontrolled bacterial growth and extracellular bacteria, ultimately resulting in loss of host resistance and increased mortality. d , HDT targeting PGE2, either directly or indirectly by enhancing PGE2 levels via 5-LO inhibition with zileuton, returns the system to a non-pathological steady state by limiting type I IFN-driven disease exacerbation, bacterial replication and pulmonary necrosis.…”
Section: Extended Datamentioning
confidence: 99%
“…This leads to excessive type I IFN expression that in turn causes increased bacterial replication and pathology, thus modelling the type I IFN-associated uncontrolled active disease that occurs in a subset of TB patients 2022 . c , Likewise, experimental induction of type I IFNs by pICLC or viral co-infections 33 creates a detrimental environment with uncontrolled bacterial growth and extracellular bacteria, ultimately resulting in loss of host resistance and increased mortality. d , HDT targeting PGE2, either directly or indirectly by enhancing PGE2 levels via 5-LO inhibition with zileuton, returns the system to a non-pathological steady state by limiting type I IFN-driven disease exacerbation, bacterial replication and pulmonary necrosis.…”
Section: Extended Datamentioning
confidence: 99%
“…The difference between the effects of type I and type III IFNs might be important especially in the context of viral-bacterial coinfection, which is seen frequently during influenza virus infections, for example, and can lead to severe disease 84,85 . Therefore, type III IFN is keeping the borders clear of viral infection without causing widespread immune activation, but it could also be better than type I IFN in steering clear of interfering with the antibacterial immune responses required during polymicrobial exposure.…”
Section: Type III Ifn and Coinfectionmentioning
confidence: 99%
“…Mouse models have shown that prior exposure to influenza A impairs immune responses to Mtb infection and decreases survival (Redford et al 2014), possibly through down-regulated MHC (major histocompatibility complex) expression on dendritic cells and reduced activation of CD4 and CD8 T cells to clear mycobacteria (Florido et al 2013). A similar murine study found influenza had little effect on mycobacterial load (Co et al 2006).…”
Section: Influenzamentioning
confidence: 99%